Eutrophication in Indonesian Aquatic Systems: Causes and Ecological Consequences - Cut Sarah Rizkita Rahmi; Lili Nitami; Wahdini Wahdini; Firdus Firdus; M. Nasir; Alia Rizki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Eutrophication is one of the major environmental problems affecting the quality and sustainability of aquatic ecosystems. Excessive inputs of nutrients, particularly nitrogen and phosphorus, can accelerate water fertility and lead to changes in aquatic community structure as well as a decline in water quality. This study aims to review the causes, indicators, and ecological impacts of eutrophication in various aquatic ecosystems in Indonesia. The study employed a literature review approach by analyzing scientific articles obtained from academic databases such as Google Scholar, Garuda Kemdikbud, and ScienceDirect. The results indicate that eutrophication in Indonesian waters is mainly driven by anthropogenic activities, including domestic wastewater, agricultural runoff, aquaculture practices, and industrial activities within watershed areas. These conditions are characterized by increased nutrient concentrations, changes in phytoplankton composition, and the occurrence of algal blooms that may reduce water quality and disrupt the balance of aquatic ecosystems. Therefore, nutrient source management and continuous water quality monitoring are essential to control eutrophication and maintain the sustainability of aquatic ecosystems in Indonesia.